2015
DOI: 10.1016/j.jtcvs.2014.10.120
|View full text |Cite
|
Sign up to set email alerts
|

Predicting recurrent mitral regurgitation after mitral valve repair for severe ischemic mitral regurgitation

Abstract: Objectives The Cardiothoracic Surgical Trials Network recently reported no difference in the primary end point of left ventricular end-systolic volume index at 1 year postsurgery in patients randomized to repair (n = 126) or replacement (n = 125) for severe ischemic mitral regurgitation. However, patients undergoing repair experienced significantly more recurrent mitral regurgitation than patients undergoing replacement (32.6% vs 2.3%). We examined whether baseline echocardiographic and clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 41 publications
3
119
0
4
Order By: Relevance
“…Given the high rate of recurrent mitral regurgitation in patients after RA-repair, surgeons have to consider chordalsparing mitral-valve replacement or combined procedure with subvalvular repair and undersizing mitral annuloplasty to solve ischemic mitral disorder (9)(10)(11)(12)(13)(14). The results of the two-years randomized trial in patients with moderate and severe IMR by the Cardiothoracic Surgical Trials Network (CTSN) imposed the need to revise the surgical dogma regarding the superiority of mitral valve repair over replacement (9,10).…”
Section: Specific Surgical Perspectives In Imrmentioning
confidence: 99%
“…Given the high rate of recurrent mitral regurgitation in patients after RA-repair, surgeons have to consider chordalsparing mitral-valve replacement or combined procedure with subvalvular repair and undersizing mitral annuloplasty to solve ischemic mitral disorder (9)(10)(11)(12)(13)(14). The results of the two-years randomized trial in patients with moderate and severe IMR by the Cardiothoracic Surgical Trials Network (CTSN) imposed the need to revise the surgical dogma regarding the superiority of mitral valve repair over replacement (9,10).…”
Section: Specific Surgical Perspectives In Imrmentioning
confidence: 99%
“…20 This is traditionally attributed to a potentially excessive reduction of mitral annular area by the ring and abnormal leaflet opening function (diastolic tethering of anterior mitral leaflet). 6,7 Whether the degree of mitral stenosis created by restrictive mitral annuloplasty limits patients' exercise capacity and compromises the patient outcome remains controversial. 21,22 However, most studies have based stenosis grading on the mean transmitral pressure gradient at rest that largely underestimates the hemodynamic effect of stenosis.…”
Section: Hemodynamic Performance After Undersized Mitral Annuloplastymentioning
confidence: 99%
“…2 To date, restrictive MVA represents the most performed techniques used to treat patients with secondary MR. 3 Several studies have shown that the recurrence of MR at 1-year remains high (10%-30%). [4][5][6] Moreover, it has been reported that restrictive MVA could be associated with impaired hemodynamic profile with higher transmitral gradient and systolic pulmonary artery pressure (PAP) at exercise and worsening in functional New York Heart Association (NYHA) class. 7 Several types of prosthetic rings exist to remodel the mitral annulus.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgical annuloplasty can correct the MR for the short term, it recurs in about one third of patients at 1 year. 11 A recent randomized trial of repair versus replacement in ischemic MR demonstrated a more durable correction with valve replacement at 2 years. It is in this arena that the field of transcatheter mitral valve replacement is most commonly being used in early feasibility trials.…”
Section: Transcatheter Treatment Of Mitral Valve Diseasementioning
confidence: 99%